(3cJGH ehGRjf GdGMLGQ Ydi QCi HdjfGSs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf ai cGf PGcQkG deG PcQfGg ai GdefGRd GdChdi hGdKGfjI hGdKGdKI ai gPG GdcJGH afbhd Cf GdGQhGM eNGdaI ddCLSGe ai GdfGQ s
(3BNQgG (B:s
(3hbO cfG eSJZfjf Yf gPG GdTcd eY eG cfG YdefGc ef CeQ eNGdaI GdMQha ai ZjQ cJGH hEf cfJ jG CNj de JbQC ai cJHfG ZjQ gPg GdGQHYI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHY YTQs
(3HgG GdYOjO ef GdLOGhds
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9318) s
Keywords: (3GdadSaI hGdefWbs